PENGARUH SIKAP DAN NORMA SUBJEKTIF TERHADAP MINAT BELI KONSUMEN MIE BARACCUNG DI JALAN TENGGER KANDANGAN SURABAYA - Latifah, Siti Suryani Nur; Maduwinarti, Ayun; Mulyati, Awin (Universitas 17 Agustus 1945 Surabaya, 2019)
A business owner, in marketing his own products not only must have a strategy in running his business but also must pay attention to consumer behavior so that interest arises to consume products and services that are marketed. It is expected that consumers can repurchase at other times and recommend it to others. This study aims to determine the effect of attitudes and subjective norms on consumers purchase interest in Mie Baraccung on JalanTenggerKandangan Surabaya. The population used in this study were people who have not and have already made a purchase at the Mie Baraccung in Surabaya. The sample used amounted to 100 respondents using accidental sampling technique. Data is collected through questionnaires distributed to respondents and interviews with business owners. For data analysis used validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, correlation test, determination coefficient test (R2), partial test (t), and simultaneous test (F). All data analysis was carried out with the help of SPSS version 16.0. The results of this study indicate that there is a positive influence between attitudes and consumer buying interest, there is a positive influence between subjective norms and consumer buying interest, subjective attitudes and norms have an effect on consumers' buying interest, and attitude variables have a more dominant influence on purchase interest consumers in Mie Baraccung Surabaya.Keyword : attitudes, subjective norms, and purchase interests